'An invention…that bottled up a memory, like scent': phantom fragrances in Daphne du Maurier's Rebecca. Issue 8 (16th November 2020) - Sivinski, Stacy
ABSTRACT: In the opening chapters of Rebecca, du Maurier's unnamed narrator makes a poignant remark about her desire to re-experience certain memories: 'If only there could be an invention … that bottled up a memory, like scent. And it never faded, and it never got stale'. Although her suitor curtly dismisses this comment, readers should not be as quick to forget the tie that the narrator draws between memory and scent. In this article, I argue that fragrance is not an insignificant detail of du Maurier's story but rather an emotively charged presence that can help readers better understand the relationship between the narrator and the first Mrs. de Winter. After discussing neurological and anthropological studies that have emerged around smell's connection to memory and liminality, I explore moments in du Maurier's text where fragrances reanimate Rebecca and create a visceral connection between the protagonist and this deceased yet very much present character. By examining the way Rebecca rises to the surface through smell, I ultimately show that odours play a pivotal role in allowing readers to recognize how her forceful and resilient personality continues to dismantle the boundaries of patriarchal control from beyond the grave.